Scrotal Kaposi's sarcoma in an immunocompetent patient: A case report and review of the literature - Daifullah Al Aboud (Our Dermatology Online, 2022)
Kaposi's sarcoma (KS) is a malignancy that generally affects the skin. It may be systemic with internal organ involvement, originating from the vascular endothelium. It is an acquired immunodeficiency syndrome (AIDS)-defining illness. Human herpes virus-8 (HHV-8) infection is involved in its pathogenesis. KS lesions have a general distribution, often involving the skin of the feet and legs and, to a lesser extent, the hands, arms, and trunk. Isolated scrotal involvement in an immunocompetent patient is a highly rare presentation. Herein, we present an immunocompetent Saudi patient with scrotal KS. A review of the related literature is also presented.